Pengaruh Metode Outdoor Study Berbasis Discovery Learning Terhadap Hasil Belajar IPA Siswa Kelas IV UPT SPF SD Inpres Hombes Armed - Apriliniar, Elma; Fatimah, Waddi; Suhardianto, Suhardianto; Cayati, Cayati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research aims to determine the effect of the outdoor study method based on discovery learning on the science learning outcomes of class IV UPT SPF SD Inpres Hombes Armed students. This research is a quantitative research type of experimental research with a one group pretest-posttest design. The sample in this study was 30 class IV A students consisting of 14 men and 16 women. The sampling technique in this research is saturated sampling. The research instruments used were observation sheets, learning outcomes tests, and documentation. Data were analyzed using descriptive analysis and inferential statistical analysis with the help of the SPSS computer program. The results of this research show that the teacher's ability to apply the discovery learning-based outdoor study method to the science learning outcomes of class IV students received an average score of 3.2, which means it was implemented well. The learning outcomes of class IV A students are described from the results of the prerequisite tests which consist of normality test results of the pretest 0.007 ≥ 0.05 and posttest 0.031 ≥ 0.05 with normal distribution, homogeneity test results 0.013 ≥ 0.05 which means homogeneous and the results of the hypothesis test 0.001 with the criteria Sig (0.001) ≤ α (0.05). So the results of this research show that there is an influence of the outdoor study method based on discovery learning on the science learning outcomes of class IV students at UPT SPF SD Inpres Hombes Armed